Renal Cell Carcinoma: A Cancer-testis Antigen Poor Malignancy - Faramarzi, Sepideh; Ghafouri-Fard, Soudeh (Asian Pacific Journal of Cancer Biology, 2017)
Renal cell carcinoma (RCC) is a relatively frequent cancer with increasing incidence in some regions. There is a need for early diagnosis of this cancer as a significant number of patients develop metastasis in their clinical course. Cancer-testis antigens (CTAs) are a group of tumor associated antigens whose expression has been assessed in a wide range of malignancies. CTAs are also considered as immunotherapy targets. Considering the relative responsiveness of RCC patients to immunotherapy, expression analysis of CTAs in RCC is of clinical importance. However, data regarding expression of CTAs in RCC is scarce except for a few numbers of CTAs including NY-ESO-1. The expression pattern of CTAs in RCC samples and cell lines is reviewed in this manuscript.